Efektivitas Relokasi Pasar Dan Dampaknya Terhadap Pendapatan Pedagang Pasar Badung - Utari, Ni Made Dian; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 7, Juli 2017 (pp. 1157 - 1394), 2017)
Badung market is one of the traditional market in Denpasar which has the highest number of traders. Badung market has experienced a fire accident in February 2016 ago. The government made the relocation policy or market dislocations to Ex Tiara Wholesale Supermarket Br. Balun Denpasar. The purpose of this study are to: 1) the effectiveness of market relocation Badung seen from indicators of input, process and output, 2) to assess income market traders Badung before and after the relocation of the market, 3) to assess income market traders Badung after the relocation of the market. This research was conducted in Ex Tiara Wholesale Supermarket. Samples of this research were 93 respondents. The method used in this study include observation, structured interviews, and in-depth interviews. This research using descriptive statistical tests to see the trends of respondents' perception and inferential statistical test that is different test and Wilcoxon test. Based on the results obtained by analysis of the success rate of relocation occurs Badung Market seen from the input variables, process variables and output variables in Ex.Tiara Wholesale Supermarket is quite effective. Revenues decreased market traders after the relocation market do. From the results obtained, it is expected to accelerate the completion of Badung market that traders who are relocating the market may soon reoccupy Pasar Badung and earnings Badung market traders back to normal
Keywords: efektivitas, relokasi, pendapatan